The relationship between physical activity levels and symptoms of depression, anxiety and stress in individuals with Alopecia Areata - Rajoo, Y.; Wong, J.; Cooper, Grant; Selva Raj, I.; Castle, D.; Chong, A.; Green, J.; Kennedy, G. (Springer Nature, 2019)
Background: Alopecia Areata (AA) is an autoimmune condition that is characterised by non-scarring hair loss. Its aesthetic repercussions can lead to profound changes in psychological well-being. Although physical activity (PA) has been associated with better mental health outcomes in diverse populations, the association in individuals with AA has not been established. The aim of this study was to examine the associations between PA and mental health outcomes in individuals with AA to inform intervention strategies for this specific population.